Science Education in the Digital Era: Socioeconomic Barriers, ICT Integration and Emerging Gaps in Teaching and Learning - Opeyemi Abdullahi Alabi; Moses Adeleke Adeoye; Alani Ahmed Abiola; Muhammad Omeiza Raji (Universitas Islam Bunga Bangsa Cirebon, 2025)
The rapid advancement of digital technologies has reshaped educational practices globally, yet science education in Nigeria continues to face systemic challenges in adapting to this shift. Persistent infrastructural gaps, economic constraints, and disparities in teacher preparedness raise critical questions about how effectively digital tools can enhance science learning. This research aimed to explore the opportunities and challenges of integrating information and communication technologies (ICT) into science education in Nigeria, with a focus on understanding how digitalisation shapes access, pedagogy, and equity. The research employed a qualitative, document-based method. It synthesised findings from peer-reviewed scholarship, policy documents, and national education reports through thematic analysis, allowing for the identification of recurring patterns and emerging trends in the digital transformation of science classrooms. The results show that ICT adoption in Nigerian science education is real but uneven. Three main findings emerged: socio-economic and infrastructural barriers—such as unreliable electricity, limited internet access, and household poverty—restrict effective ICT use; while some teachers employ digital tools, their application is often limited to surface-level tasks rather than transformative, inquiry-based science learning; and new divides are emerging, as digital resources remain concentrated in urban and private schools, leaving rural and disadvantaged groups further behind. In conclusion, this research contributes by framing ICT integration not as an isolated technical issue but as an interconnected system of socio-economic, infrastructural, and pedagogical factors. Its value lies in highlighting science-specific digital needs and proposing a holistic perspective that can inform policies and practices aimed at fostering inclusive, equitable, and effective science education in the digital era.